A Dual-Morphing Pneumatic Origami Gripper - Ting Yan; Shao-Feng Xu; Kuo-Chih Chuang (Actuators)
In this work, we propose a lightweight pneumatic gripper that can grasp objects from either the outer or inner surfaces. Inspired by the Miura-ori pattern, the gripper is fabricated by laminating films with different cutting patterns to form the crease lines and air chambers. The asymmetry in the thickness of the top and bottom sides of the air chambers causes the gripper’s end to rotate in a predetermined direction upon inflation, enabling a dual-morphing grasping action. The dual morphings include an outward grasping morphing (grasping from the outer surface) and an inward grasping morphing (grasping from the inner surface). The deflection of the gripper’s end, induced by the air chamber’s inflation, is theoretically analyzed using a simplified one-dimensional model. We conducted both finite element modeling and experimental measurements to investigate the influence of the air chamber’s design parameters. Weighing only 4.5 g, the gripper can lift objects more than ten times of its own weight. This study provides a valuable design insight for developing more flexible and adaptable soft grippers capable of holding objects with a wider range of geometrical characteristics.